Michael Gallagher & Michael Marsh, eds., Candidate Selection in Comparative Perspective. - The Secret Garden of Politics, London: Sage Publications, 1988, 294 s., £ 25,00. - N. Pedersen, Mogens (Politica, 1988)
-